2007
DOI: 10.3852/mycologia.99.5.777
|View full text |Cite
|
Sign up to set email alerts
|

Heteroconium sp. nov. from roots of Triticum aestivum in the United Kingdom

Abstract: Morphological and molecular studies led to the description of Heteroconium triticicola as a new species isolated from roots of wheat in the United Kingdom. The new fungus shares with H. citharexyli, the type species of Heteroconium Petrak, features such as superficial mycelium, macronematous, mononematous, unbranched, straight conidiophores, monoblastic, integrated, terminal, cylindrical conidiogenous cells, and catenate, dry, simple, cylindrical, obclavate, often pale brown, smooth, multiseptate conidia. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Heteroconium triticicola, which was isolated from roots of wheat in the U. K., was found to be phylogenetically similar to the mycorrhizal ascomycete family Hyaloscyphaceae (Kwasna and Bateman 2007). Results from molecular studies on Herpotrichiellaceae and Venturiaceae fungi indicated that H. chaetospira, which is commonly found on rotting wood in Europe (Ellis 1976), showed a much higher phylogenetic similarity to Chaetothyriales, and was thus placed in Cladophialophora (Crous et al 2007b).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Heteroconium triticicola, which was isolated from roots of wheat in the U. K., was found to be phylogenetically similar to the mycorrhizal ascomycete family Hyaloscyphaceae (Kwasna and Bateman 2007). Results from molecular studies on Herpotrichiellaceae and Venturiaceae fungi indicated that H. chaetospira, which is commonly found on rotting wood in Europe (Ellis 1976), showed a much higher phylogenetic similarity to Chaetothyriales, and was thus placed in Cladophialophora (Crous et al 2007b).…”
Section: Discussionmentioning
confidence: 93%
“…Several recent studies have suggested that Heteroconium has affinities to diverse orders, and is polyphyletic (Crous et al 2007a;Kwasna and Bateman 2007). Heteroconium triticicola, which was isolated from roots of wheat in the U. K., was found to be phylogenetically similar to the mycorrhizal ascomycete family Hyaloscyphaceae (Kwasna and Bateman 2007).…”
Section: Discussionmentioning
confidence: 98%